A Pengaruh Penggunaan Media Visual Terhadap Minat Belajar Anak Di Kelompok B1 TK Nusa Kota Makassar - Angri Lismayani (LPPM Universitas Muhammadiyah Cirebon, 2023)
This research aims to determine the profile of children's learning interest before and after the use of visual media in Group B1 of Nusa Kota Makassar Kindergarten. The approach used in this research is a quantitative approach. The type of research used is a pre-experimental design, specifically a one-group pretest-posttest design. The sample used in this study consists of 10 children. Data collection techniques include observation, interviews, and documentation. The data analysis technique used is descriptive statistical analysis and non-parametric statistics using the Wilcoxon test. The results of the study indicate that there is a difference in the average value of children's learning interest before and after treatment. This indicates the influence of the use of visual media on children's learning interest in Group B1 of Nusa Kota Makassar Kindergarten. Keywords : learning media, visual media, interest learn